Reaming the intramedullary canal during tibial nailing does not affect in vivo intramuscular pH of the anterior tibialis - Black, Loren O.; Rushkin, Megan; Lancaster, Karalynn; Cheesman, J. Samuel; Meeker, James E.; Yoo, Jung U.; Friess, Darin M.; Working, Zachary M. (OTA international : the open access journal of orthopaedic trauma, 2023)
Many investigations have evaluated local and systemic consequences of intramedullary (IM) reaming and suggest that reaming may cause, or exacerbate, injury to the soft tissues adjacent to fractures. To date, no study has examined the effect on local muscular physiology as measured by intramuscular pH (IpH). Here, we observe in vivo IpH during IM reaming for tibia fractures. Adults with acute tibia shaft fractures (level 1, academic, 2019-2021) were offered enrollment in an observational cohort. During IM nailing, a sterile, validated IpH probe was placed into the anterior tibialis (<5 cm from fracture, continuous sampling, independent research team). IpH before, during, and after reaming was averaged and compared through repeated measures ANOVA. As the appropriate period to analyze IpH during reaming is unknown, the analysis was repeated over periods of 0.5, 1, 2, 5, 10, and 15 minutes prereaming and postreaming time intervals. Sixteen subjects with tibia shaft fractures were observed during nailing. Average time from injury to surgery was 35.0 hours (SD, 31.8). Starting and ending perioperative IpH was acidic, averaging 6.64 (SD, 0.21) and 6.74 (SD, 0.17), respectively. Average reaming time lasted 15 minutes. Average IpH during reaming was 6.73 (SD, 0.15). There was no difference in IpH between prereaming, intrareaming, and postreaming periods. IpH did not differ regardless of analysis over short or long time domains compared with the duration of reaming. Reaming does not affect IpH. Both granular and broad time domains were tested, revealing no observable local impact.